Probing Meaning Loss in the Translation of Qur’anic Cognitive Terms into Indonesian and English: A Componential and Comparative Analysis - Sholahudin, Shofwan; Al Farisi, Mohamad Zaka; Haeba, Ilham Dwitama (Institut Agama Islam Negeri (IAIN) Keiri, 2025)
Translating the Qur'an is a complex task that requires not only linguistic accuracy but also sensitivity to semantic and spiritual meanings. One of the major challenges in Qur'anic translation lies in rendering cognitive terms such as tafakkur, tadabbur, and ʿaql, which possess complex and multifaceted semantic dimensions. This study aims to identify the diagnostic and supplementary semantic features of these three terms using the Componential Analysis (CA) approach. In addition, it evaluates their lexical equivalents in two Indonesian and two English Qur'anic translations to assess semantic equivalence. The findings reveal that although the three terms share cognitive and contemplative features, each reflects distinct orientations and functions: tafakkur emphasizes exploratory thinking about observable phenomena; tadabbur involves deductive reflection on the implicit meanings of verses; and ʿaql denotes evaluative reasoning grounded in knowledge. The translation assessment indicates that the Hilali & Khan and Saheeh International versions provide the most semantically accurate renderings, whereas the Kemenag and Muhammad Thalib translations exhibit certain limitations. These results highlight the importance of a semantic-based approach in Qur'anic translation to preserve the depth and accuracy of the Qur'an's cognitive–spiritual message. This study contributes to the cross-linguistic understanding of the semantic nuances of Qur'anic cognitive terms and provides a methodological foundation for further research on meaning transfer and translation strategies in Qur'anic exegesis and translation studies.